Initial steps towards an evidence-based classification system for golfers with a physical impairment. Issue 2 (16th January 2017) - Stoter, Inge K.; Hettinga, Florentina J.; Altmann, Viola; Eisma, Wim; Arendzen, Hans; Bennett, Tony; van der Woude, Lucas H.; Dekker, Rienk
Abstract: Purpose : The present narrative review aims to make a first step towards an evidence-based classification system in handigolf following the International Paralympic Committee (IPC). It intends to create a conceptual framework of classification for handigolf and an agenda for future research. Method : Pubmed was searched on three themes: "Classification in Paralympic sports", "Performance determining factors in golf" and "Impact of impairments on golf performance". IPC-regulations were gathered on the IPC-website and their official publications. Results : In developing a classification system conform IPC-regulations, the main challenge is to identify the activity limitation caused by the impairment, not influenced by training, talent or motivation. Timing, accuracy and control, work per joint, range of motion, balance and flexibility are important performance determining factors in abled-bodied golf and should be considered when determining activity limitations in handigolf. Only five articles on handigolf were found, mainly addressing the asymmetric golf movement. Based on the present review, a conceptual framework for classification was developed, while a future research agenda was designated. The conceptual framework presents factors that are essential for sports performance categorized under "technology", "interface" and "athlete characteristics". It also includes impairment related factors essential for determining eligibility and classification. Ideally, measures to be used during classification need to be resistant against training, natural development of the athlete's talent and motivational changes. Conclusions : The conceptual framework and a multidimensional scientific research agenda will support further development of the knowledge base required for an evidence-based classification in handigolf, including multi-level analysis of player statistics, experimental analyses of biomechanics and modeling studies. Implications for Rehabilitation: The main challenge in developing an evidence-based classification system conform IPC-regulations is defining eligibility criteria and sport classes based on activity limitation caused by only the impairment and not affected by training, talent and motivation. It is expected that a transparent classification system, a lively competition and admission to the Paralympic program will further promote participation in disabled golf. Timing, accuracy and control, work per joint, range of motion, balance and flexibility are of greater importance for golf performance in able-bodied golfers and expected to be of interest to incorporate in classification for handigolf. Side and level of amputation influence activity limitation in the asymmetric golf movement, and should be incorporated in classification. The proposed conceptual framework is fundamental to the research agenda that must further generate the knowledge-base to determine activity limitations caused by different impairments in handigolf and may serve as a guideline for other Paralympic sports in the development of evidence-based classification.